Municipal tree management in a Nigerian university (2008)
There is a growing recognition that municipal trees improve the quality of life in many ways through the provision of both goods and services. For proper tapping of the benefits, urban residents also need to manage the municipal trees sustainability. Thus, the study is carried out to assess the management technique for the municipal trees in University of Ibadan campus. A technical assessment of the activities of the operations crew of the Campus Tree Management Committee saddled with the responsibility of managing the trees was carried out for a period of five years. Using a checklist and job profile form, information were collected on tools and equipment used by the tree management committee; number of request per year: location and number of treated cases; species of the treated cases; type of treatment provided; working conditions of the crew and methods adopted; efficiency of the operation; and hazards and safety of the operations team. Data collected were analyzed wing descriptive statistics. The study revealed that all the stakeholders appreciated the importance of the municipal tree on campus. Fifty eight percent of the requests and 100% of emergency cases were attended to and a total of 369 trees of different species were treated. The crew members are experienced in urban tree management, but there is need to procure modern equipment for tree management in residential areas to reduce the work stress and hazards of the job. There is need to involve the entire University community in the management of the trees through development of policies that will minimize the disturbance of municipal trees, promote a tree friendly attitude in relation to development and expansion. Considering the number of dangerous trees being removed presently on the campus, there is therefore the urgent need to improve on the effort to plant new trees.